2007
DOI: 10.1001/archopht.125.7.945
|View full text |Cite
|
Sign up to set email alerts
|

Health-Related Quality of Life and Utility in Patients With Age-Related Macular Degeneration

Abstract: To assess the impact of best-eye and worst-eye visual acuity (BEVA and WEVA, respectively) on health-related quality of life and utility in patients with wet age-related macular degeneration.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
21
0
2

Year Published

2011
2011
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(25 citation statements)
references
References 50 publications
2
21
0
2
Order By: Relevance
“…The construct validity of the EQ-5D, TTO, and SG was assessed by testing a priori hypotheses relating utility scores with clinical indices of disease severity. Current literature shows that utility measures (eg, TTO and SG) correlate better with disease indices than generic health status instruments (eg, EQ-5D), 5,16,[18][19][20][21] and clinical AMD severity correlates poorly on utility measures and EQ-5D. 22,23 Therefore, we hypothesised that (1) EQ-5D would correlate weakly to moderately well with VA and clinical AMD severity, (2) TTO and SG would show a moderate to strong correlation with VA, but null to weak correlation with clinical AMD severity.…”
Section: Statistical Analysesmentioning
confidence: 99%
“…The construct validity of the EQ-5D, TTO, and SG was assessed by testing a priori hypotheses relating utility scores with clinical indices of disease severity. Current literature shows that utility measures (eg, TTO and SG) correlate better with disease indices than generic health status instruments (eg, EQ-5D), 5,16,[18][19][20][21] and clinical AMD severity correlates poorly on utility measures and EQ-5D. 22,23 Therefore, we hypothesised that (1) EQ-5D would correlate weakly to moderately well with VA and clinical AMD severity, (2) TTO and SG would show a moderate to strong correlation with VA, but null to weak correlation with clinical AMD severity.…”
Section: Statistical Analysesmentioning
confidence: 99%
“…The 25-item National Eye Institute Visual Function Questionnaire (NEI-VFQ-25) is a 25-item generic, vision-related QoL instrument that has already been used with AMD [10,11]. …”
Section: Introductionmentioning
confidence: 99%
“…A crosssectional European study of best eye and worst eye visual acuity in patients with age-related macular degeneration (ARMD) showed that vision loss is strongly associated with decreased health-related quality of life. 1 This calls for the primary eye care provider to address treatment options for the whole person, not just the eye disease. For patients with visual impairment, low vision services are an essential part of the treatment plan.…”
Section: The Need For Vision Rehabilitationmentioning
confidence: 99%